Cardiotoxicity in relation to treatment with aromatase inhibitors in breast cancer. (February 2022) - Lund, Marie; Ejlertsen, Bent
Abstract : Summary: With the success of modern cancer therapy, breast cancer survival has steadily improved over the last decades. Treatment with aromatase inhibitors has become the preferred endocrine treatment in postmenopausal women with estrogen receptor-positive breast cancer. However, concerns have been raised over a possible cardiotoxic potential. The aim of the current paper is to review the evidence regarding cardiotoxicity with aromatase inhibitors in breast cancer. Weighing benefits vs. risks, the improved effect of aromatase inhibitors vs. tamoxifen on breast cancer recurrence in most patients outweighs the potential risk of CV adverse events. At present it is advisable to ensure that standard measures of cardiovascular disease (CVD) management are applied to women with breast cancer, i.e., lifestyle intervention and if needed medical treatment of CVD and risk factors for CVD.